PELATIHAN DAN PENDAMPINGAN PENULISAN ARTIKEL ILMIAH DAN PUBLIKASI JURNAL ILMIAH BAGI GURU SEKOLAH DASAR - Bintoro, Henry Suryo; Purwaningrum, Jayanti Putri; Sumaji, Sumaji; Wanabuliandari, Savitri; Rahayu, Ratri (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
The aim of this service activity is to optimize the teacher's ability to understand writing scientific articles as well as knowing how to publish them in scientific journals. With the guidance of the facilitator, teachers are expected to be able to write scientific articles and publish them in scientific journals. The target of this service is to provide technological knowledge related to how to publish articles in scientific journals to partner elementary school teachers by providing knowledge and skills to elementary school 4 teachers in Karangmalang, Kudus Regency in the form of interactive training and assistance in scientific article writing training and training and assistance in publishing in scientific journals. The method used in this service includes several stages, including: planning, implementation, follow-up (products resulting from training and mentoring), simulation, practice and evaluation. The result of this activity was that the teachers at SD 4 Karangmalang, Kudus Regency were able to design, create and publish scientific articles in scientific journals.